Ellipsis As Aesthetic Formal Marker of the Short Story Das Brot - ., Rosyidah (KnE Social Sciences, 2019)
In the short story Das Brot, the use of ellipsis is dominant. Therefore, it is considered as formal aesthetic marker of this literary text. This paper is based on the results of the research which aimed (1) to describe the ellipsis used by the author in the short story and (2) to describe the aesthetic functions of these ellipsis. Analysis covered all syntactically incomplete sentences in the short story. Furthermore, the aesthetic functions of the ellipsis were analysed qualitatively. The research concludes that in the short story, ellipsis refer to sentences without subject and predicate; subject, predicate and predicative adjectivephrases; subject, predicate and object; object; adverbs and also sentences without main clause. The research results also show that the ellipsis in the short story have aesthetic interactive functions which relate to intersubjectivity and continuer. Moreover, it has also communicative functions, specifically expressive, assertive and directive functions. In the short story Das Brot, the use of ellipsis is dominant. Therefore, it is considered as formal aesthetic marker of this literary text. This paper is based on the results of the research which aimed (1) to describe the ellipsis used by the author in the short story and (2) to describe the aesthetic functions of these ellipsis. Analysis covered all syntactically incomplete sentences in the short story. Furthermore, the aesthetic functions of the ellipsis were analysed qualitatively. The research concludes that in the short story, ellipsis refer to sentences without subject and predicate; subject, predicate and predicative adjectivephrases; subject, predicate and object; object; adverbs and also sentences without main clause. The research results also show that the ellipsis in the short story have aesthetic interactive functions which relate to intersubjectivity and continuer. Moreover, it has also communicative functions, specifically expressive, assertive and directive functions. Keywords: ellipsis, formal aesthetic marker, function, short story Das Brot